(untitled) (Tabanque. Revista Pedagógica, 2020)
In Kabare chiefdom in Democratic Republic of Congo, the population is languishing in extreme poverty as a result of the marginalization of women by the patriarchal social structure, illiteracy, war, lack of social policy of the government, lack of initiative and training of the population. The goal of this project is to weaken the aforementioned social structure by the people empowerment through literacy training that initiates a process of community development that concretizes gender equality and productive output to solve the problems that suffocate families. For that, literacy will be imbued with the pedagogy of problems, set up by Paulo Freire, and based on the dialectic theory-practice. It is concretized by reflective-critical debates on the social reality, actions-evaluations, in order to eliminate dichotomy between literacy and real life, this trap to which adult literacy programs generally succumb.